ESL Reading Accuracy: The Inside Story - Rafizah Mohd Rawian; Ahmad Azman Mokhtar (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2016)
Accuracy has received countless and endless attention from language researchers due to its role in language learning. As such, a study is conducted to discover and understand the possible influence of accuracy in second language learning specifically in reading. Its findings will reveal whether accuracy does actually affect reading or vice versa. Simultaneously, the findings will then expose the extent of the possible influence as well as the aspects that may be affected. Its respondents are students who are taking Basic English Language course. Purposeful random sampling technique is used to single out the respondents in terms of their (1) gender and (2) academic semester. An in-depth interview protocol is used to gather data from the selected respondents. An interview checklist is used to ensure the smoothness of the data gathering. An interview guide is prepared beforehand to ensure all important issues are explored. The interview questions are prepared in two versions: English and Malay language.